2012
DOI: 10.1111/j.1467-8624.2012.1780.x
|View full text |Cite
|
Sign up to set email alerts
|

Child‐Care Subsidies: Do They Impact the Quality of Care Children Experience?

Abstract: The federal child-care subsidy program represents one of the government's largest investments in early care and education, but little is known about whether it increases low-income children's access to higher quality child care. This study used newly available nationally representative data on 4-year-old children (N = 750) to investigate whether subsidy receipt elevates child-care quality. Results indicate that subsidy recipients use higher quality care compared to nonrecipients who use no other publicly funde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 77 publications
(66 citation statements)
references
References 50 publications
1
64
1
Order By: Relevance
“…Subsidies also represent added household income, which not only reduces parents' stress but also allows them to purchase materials and activities that promote school readiness (e.g., Conger, Conger, & Elder, ; Dearing & Taylor, ; Gershoff, Aber, Raver, & Lennon, ). However, a recent study comparing subsidy recipients to eligible nonrecipients found that subsidies were associated with higher quality child care in only a select portion of the population (Johnson, Ryan, & Brooks‐Gunn, ). Moreover, to the extent that subsidies increase child‐care quality, they may not yield enough of an increase to contribute to children's school readiness.…”
Section: Possible Links Between Child‐care Subsidies and Later Schoolmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsidies also represent added household income, which not only reduces parents' stress but also allows them to purchase materials and activities that promote school readiness (e.g., Conger, Conger, & Elder, ; Dearing & Taylor, ; Gershoff, Aber, Raver, & Lennon, ). However, a recent study comparing subsidy recipients to eligible nonrecipients found that subsidies were associated with higher quality child care in only a select portion of the population (Johnson, Ryan, & Brooks‐Gunn, ). Moreover, to the extent that subsidies increase child‐care quality, they may not yield enough of an increase to contribute to children's school readiness.…”
Section: Possible Links Between Child‐care Subsidies and Later Schoolmentioning
confidence: 99%
“…Moreover, the subsidy‐eligible population disproportionately represents single mothers (Herbst, ), whose children are more likely to experience multiple, simultaneous child‐care arrangements (Morrissey, ). Thus, even if subsidy recipients experience higher quality of care than nonrecipients in unsubsidized care (Johnson et al., ), they may do so for only a short time, or have additional child‐care arrangements that are low quality.…”
Section: Possible Links Between Child‐care Subsidies and Later Schoolmentioning
confidence: 99%
“…Parents who received subsidies enrolled their 3‐year‐olds in higher quality care than nonrecipients who were eligible for subsidies and matched on propensity scores, a finding driven by increased use of center‐based care among subsidy recipients. Nationally representative studies of toddlers and preschoolers replicated these methods and results. In the latter study, a more nuanced pattern of results emerged because the comparison group for preschool‐aged children whose parents received subsidies expanded to include low‐income children in Head Start and public pre‐k (who themselves may have received subsidies at an earlier age; ).…”
Section: Child‐care Subsidies and Child‐care Qualitymentioning
confidence: 64%
“…Those who prioritized having a caregiver who would speak English with the child were more likely to select Head Start or public pre-k compared to unsubsidized ECE. It is not surprising that low-income families who prioritize school readiness are more likely to choose Head Start settings, given prior research showing that, compared to other types of settings used by low-income families, Head Start settings tend to score higher when it comes to developmental quality of care provided (Johnson, Ryan, & Brooks-Gunn, 2012). Perhaps mothers with these preferences who chose subsidized or unsubsidized ECE did so because they believed these programs offered similar benefits.…”
Section: Discussionmentioning
confidence: 99%